Economic evaluation of a participatory return-to-work intervention for temporary agency and unemployed workers sick-listed due to musculoskeletal disorders - Sylvia J Vermeulen; Martijn W Heymans; Johannes R Anema; Antonius JM Schellart; Willem van Mechelen; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aim of the study was to evaluate the cost-effectiveness, -utility, and -benefit of a newly developed participatory return-to-work (RTW) program for temporary agency and unemployed workers, sick-listed due to musculoskeletal disorders. METHODS: An economic evaluation was conducted alongside a randomized controlled trial with a 12-month follow-up. Temporary agency and unemployed workers, sick-listed for 2â€"8 weeks due to musculoskeletal disorders, were randomized to the participatory RTW program (N=79) or usual care group (N=84). The new RTW program was aimed at making a consensus-based RTW action plan with the possibility of a temporary (therapeutic) workplace. Effect outcomes were sustainable RTW and quality-adjusted life years (QALY). Healthcare utilization was measured from the social insurerâ€™s perspective and societal perspective. RESULTS: Total healthcare costs in the participatory RTW program group [10 189 (standard deviation [SD] 7055) euros] were statistically significantly higher compared to care-as-usual [7862 (SD 7394) euros]. The cost-effectiveness analyses showed that the new intervention was more effective but also more costly than usual care (ie, to gain RTW one day earlier in the participatory RTW program group approximately 80 euros needed to be invested). The net societal benefit of the participatory RTW program compared to care-as-usual was 2073 euros per worker. CONCLUSIONS: The newly developed participatory RTW program was more effective but also more costly than usual care. The program enhanced work resumption and generated a net socioeconomic benefit. Hence, implementation of the participatory RTW program may have potential to achieve a sustainable contribution of vulnerable workers to the labor force.